2020
DOI: 10.1038/s41598-020-76151-w
|View full text |Cite
|
Sign up to set email alerts
|

Anti-herpes virus activity of the carnivorous botanical, Sarracenia purpurea

Abstract: Herpes simplex virus type-1 (HSV-1), one of the most widely spread human viruses in the Herpesviridae family, causes herpes labialis (cold sores) and keratitis (inflammation of the cornea). Conventional treatment for HSV-1 infection includes pharmaceutical drugs, such as acyclovir and docosonal, which are efficacious but maintain the potential for the development of viral drug resistance. Extracts from the carnivorous pitcher plant, Sarracenia purpurea, have previously been shown to inhibit the replication of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Within this time frame, there were two (1.46%) studies in 2015 [ 6 , 7 ], 15 (10.95%) studies in 2016 [ 1 , 3 , 8 - 20 ], 19 (13.87%) studies in 2017 [ 21 - 39 ], 27 (19.71%) studies in 2018 [ 40 - 64 ], 23 (16.79%) studies in 2019 [ 2 , 65 - 86 ], 24 (17.52%) studies in 2020 [ 87 - 110 ], and 27 (19.70%) studies in 2021 [ 111 - 137 ]. Regarding the type of studies reviewed, 121 (88.32%) studies included in vitro elements [ 2 , 3 , 6 - 12 , 14 - 20 , 23 - 26 , 28 - 42 , 44 - 47 , 49 - 56 , 58 - 64 , 66 , 68 - 72 , 74 - 77 , 79 , 80 , 82 - 87 , 89 - 118 , 120 , 122 - 133 , 135 - 139 ] and 23 (16.79%) in vivo [ 2 , 13 , 15 , 18 , 22 , 25 , 27 , 28 , 37 , 43 , 48 , 56 , 62 , 67 , 73 , 78 , 81 , 100 , …”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this time frame, there were two (1.46%) studies in 2015 [ 6 , 7 ], 15 (10.95%) studies in 2016 [ 1 , 3 , 8 - 20 ], 19 (13.87%) studies in 2017 [ 21 - 39 ], 27 (19.71%) studies in 2018 [ 40 - 64 ], 23 (16.79%) studies in 2019 [ 2 , 65 - 86 ], 24 (17.52%) studies in 2020 [ 87 - 110 ], and 27 (19.70%) studies in 2021 [ 111 - 137 ]. Regarding the type of studies reviewed, 121 (88.32%) studies included in vitro elements [ 2 , 3 , 6 - 12 , 14 - 20 , 23 - 26 , 28 - 42 , 44 - 47 , 49 - 56 , 58 - 64 , 66 , 68 - 72 , 74 - 77 , 79 , 80 , 82 - 87 , 89 - 118 , 120 , 122 - 133 , 135 - 139 ] and 23 (16.79%) in vivo [ 2 , 13 , 15 , 18 , 22 , 25 , 27 , 28 , 37 , 43 , 48 , 56 , 62 , 67 , 73 , 78 , 81 , 100 , …”
Section: Reviewmentioning
confidence: 99%
“…Sample size was extremely variable and unable to be compared due to the differences in study designs. In terms of sample characteristics, 99 (72.26%) studies used Vero cells [ 2 , 3 , 6 , 8 - 10 , 14 - 20 , 23 , 25 , 26 , 28 , 30 - 34 , 36 , 39 - 42 , 44 - 47 , 50 , 51 , 53 - 56 , 58 - 64 , 66 - 70 , 72 , 74 , 76 , 77 , 79 , 82 , 83 , 85 - 87 , 89 - 95 , 97 - 108 , 111 - 113 , 115 - 118 , 120 , 122 , 123 , 125 - 130 , 132 , 133 , 135 , 137 , 138 ], 41 (29.93%) used human cell lines [ 7 , 11 , 12 , 16 , 19 , 24 , 29 , 31 , 36 , 38 , 47 , 49 , 52 - 56 , 61 , 62 , 67 ,…”
Section: Reviewmentioning
confidence: 99%
“…Kannan et al (2020) demonstrated that S. purpurea extracts are able to hinder the replication of HSV-1 by two mechanisms of action, which are through (1) inhibiting extracellular virions or viral attachment to the human host cell and (2) inhibiting the expression of viral immediateā€“early, early, and late genes when added at various times post-infection. This botanical has also previously been shown to inhibit the replication of poxviruses via the early inhibition of viral gene transcription [ 110 ].…”
Section: Medicinal Plant For Treating Dermatology-related Virusesmentioning
confidence: 99%
“…S. purpurea L. is well known as Cree medicinal plant (Cieniak et al, 2015). The plants from Sarracenia genus were found to possess antioxidant, antidiabetic, antiviral and antibacterial constituents (Kannan et al, 2020;Muhammad et al, 2013, Cieniak et al, 2015, among them sarracenin (Hu et al, 2009), betulinic acid, ursolic acid (Cieniak et al, 2015), hyperoside (quercetin-3-O-galactoside), morroniside (Harris et al, 2012) and many others were detected and con rmed (Table 1). Because hairy roots cultures are promising method for the production of interesting secondary metabolites in plants (Tian, 2015) and these cultures can be applied for enhanced synthesis of bioactive compounds, the aim of this study was to establish the tissue culture of Sarracenia purpurea L. plants and transformation of them via agroinfection method with Agrobacterium rhizogenes strain.…”
Section: Introductionmentioning
confidence: 96%